ANALISIS KEMAMPUAN PEMECAHAN MASALAH DAN KOMUNIKASI MATEMATIK PADA MATERI HIMPUNAN - Risna Deviyani; Anggrianti Anggrianti (Journal on Education, 2019)
The purpose of this study was to analyze the problem solving and mathematical communication skills of junior high school students in set material. Problem solving skills and mathematical communication skills are an important mathematical ability and need to be mastered by students who study mathematics. Therefore researchers want to conduct research that aims to describe the ability of problem solving and mathematical communication. This research was conducted on class VII students of SMPNegeri 01 Cililin with 35 students. The test instruments were given as many as 4 problem-solving ability test questions and 4 test questions mathematical communication skills that were explained. Based on the results of the test of problem solving ability and mathematical communication skills of SMPNegeri 01 Cililin students are still relatively low.